Ruttplanering för vinterväghållning - Blomlöf, Linus (2011)
This report is the final part within my education, Industrial Engineering focusing on Industrial Logistics at Luleå University of Technology. The field of this thesis is route planning for sanding during winter season (which vehicle should be used for which road). The project has been accomplished in cooperation with Company C. The purpose of this thesis is to map the flow of sand from source to destination roads and also evaluate the different modes of transportation and vehicles for sanding. For every “go-around” an amount of 22,3 ton sand is needed in the two areas that are studied within this report. In order to fulfill the purpose of the thesis the author has mapped the process of sand and evaluated different alternatives for distribution to terminals and for sanding the road network. In order to obtain a comparison of how different alternatives would affect the transportations and the costs, analysis with the load-distance method was made. According to Segerstedt (2009) the method of load-distance is very useful when finding the best location of a terminal. The analysis of the present situation and the results from the calculations shows potentials for great improvements of saving time when introducing truck for sanding instead of only tractors. Even cost for transportation will decrease with the combination of tractors and trucks because of the possibility for truck to collect the sand directly from Silo instead of different Terminals. As a recommendation Company C should try cooperate with the Purchaser about transportation of sand. It is possible to achieve a win-win situation if the routes can be changed a little bit. Suggestions in this report is to drive directly to terminal type 1 and 2 from source instead of drive to silo and empty the truck and then fill another truck that drives to terminals of type 1 and 2. Validerat; 20110614 (anonymous)